Simultaneous Determination of Cortisol and Testosterone from Rat Serum by Liquid Chromatography-Tandem Mass Spectrometry - Van Khanh, Nguyen; Thi Thanh Binh, Nguyen; Kim Thu, Dang; Thao Linh, Dao; Thi Ngoc Anh, Vu; Thi Thu Giang, Vu; Honma, Sejiro (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 1, 2022)
A liquid chromatography-electrospray ionization tandem mass spectrometry in a positive mode (LC-ESI-MS/MS) was developed to determine simultaneously the levels of cortisol and testosterone in rat serum. The MRM (Multiple Reaction Monitoring) was used to optimize ion precursor, fragmentor voltage, ion product, and collision energy. Analytical samples were treated by solid-phase extraction with Bond Elut C18 cartridge. The method was validated according to FDA guidance for bioanalytical method validation. The results indicated that this method showed a wide linearity range (0.1-100 ng/mL for cortisol and 0.025-100 ng/mL for testosterone), good linearity (r 2 > 0.999), low limit of quantification (LLOQ values of cortisol and testosterone were 0.1 ng/mL and 0.025 ng/mL, respectively), good recovery (90.4% - 108.0%), suitable repeatability (CV values were in the range of 2.7% - 14.8%), good stability in different conditions. The validated method was applied to quantify cortisol and testosterone levels in several rat blood samples. Keywords: LC-ESI-MS/MS, cortisol, testosterone, rat serum, solid-phase extraction. References [1] A. V. Rincon et al., Measuring Urinary Cortisol and Testosterone Levels in Male Barbary Macaques: A Comparison of EIA and LC-MS, General and Comparative Endocrinology, Vol. 281, 2019, pp. 117-125, https://doi.org/10.1016/j.ygcen.2019.05.017. [2] D. French, Advances in Bioanalytical Techniques to Measure Steroid Hormones in Serum, Bioanalysis, Vol. 8, No. 11, 2016, pp. 1203-1219, https://doi.org/10.4155/bio-2015-0025. [3] M. Kaleta et al., Analytical Methods for the Determination of Neuroactive Steroids, Biomolecules, Vol. 11, No. 4, 2021, pp. 1-23, https://doi.org/10.3390/biom11040553. [4] M. Závada, K. Šafarčik, O. Topolčan, Some Problems of Radioimmunoassay Control, Journal of Radioanalytical Chemistry, Vol. 46, No. 1, 1978, pp. 57-66. [5] K. S. Leung, B. M. Fong, LC-MS/MS in the Routine Clinical Laboratory: has its time come?, Anal Bioanal Chem, Vol. 406, No. 9-10, 2014, pp. 2289-2301, https://doi.org/10.1007/s00216-013-7542-5. [6] C. Shackleton, Clinical Steroid Mass Spectrometry: a 45-year History Culminating in HPLC-MS/MS Becoming an Essential Tool for Patient Diagnosis, J Steroid Biochem Mol Biol, Vol. 121, No. 3-5, 2010, pp. 481-490, https://doi.org/10.1016/j.jsbmb.2010.02.017. [7] K. Yamashita et al., Development of Sensitive Derivatization Method for Aldosterone in Liquid Chromatography–Electrospray Ionization tandem Mass Spectrometry of Corticosteroids, Journal of Chromatography A, Vol. 1200, No. 2, 2008, pp. 114-121, https://doi.org/10.1016/j.chroma.2008.05.034. [8] K. Yamashita et al., Highly Sensitive Determination of Estrone and Estradiol in Human Serum by Liquid Chromatography–Electrospray Ionization tandem Mass Spectrometry, Steroids, Vol. 72, No. 11-12, 2007, pp. 819-827, https://doi.org/10.1016/j.steroids.2007.07.003. [9] K. Yamashita et al., Development of Highly Sensitive Quantification Method for Testosterone and Hihydrotestosterone in Human Serum and Prostate Tissue by Liquid Chromatography-Electrospray Ionization Tandem Mass Spectrometry, Steroids, Vol. 74, No. 12, 2009, pp. 920-926, https://doi.org/10.1016/j.steroids.2009.06.007. [10] U. S. Department of Health and Human Services Food and Drug Administration, Center for Drug Evaluation and Research, Center for Veterinary Medicine, Bioanalytical Method Validation - Guidance for Industry, 2018. [11] M. Toukh, S. P. Gordon, M. Othman, Construction Noise Induces Hypercoagulability and Elevated Plasma Corticosteroids in Rats, Clin Appl Thromb Hemost, Vol. 20, No.7, 2014, pp. 710-715, https://doi.org/10.1177/1076029613483168. [12] L. H. Heywood, Testosterone Levels in the Male Laboratory Rat: Variation under Experimental Conditions, Int J Androl, Vol. 3, No. 5, 1980, pp. 519-529, https://doi.org/10.1111/j.1365-2605.1980.tb00140.x. [13] L. J. Mentzel, G. Wiedemann, Establishment of Reference Ranges for Cortisol in Neonates, Infants, Children and Adolescents, Eur. J. Clin. Chem. Clin. Biochem, Vol 31, No. 8, 1993, pp. 525-529, https://doi.org/10.1515/cclm.1993.31.8.525. [14] A. E. Kulle et al., A Novel Ultrapressure Liquid Chromatography Tandem Mass Spectrometry Method for the Simultaneous Determination of Androstenedione, Testosterone, and Dihydrotestosterone in Pediatric Blood Samples: Age- and Sex-specific Reference Data, J Clin Endocrinol Metab, Vol. 95, No. 5, 2010, pp. 2399-2409, https://doi.org/10.1210/jc.2009-1670. [15] A. L. Southren et al., Plasma Production Rates of Testosterone in Normal Adult Men and Women and in Patients with the Syndrome of Feminizing Testes, The Journal of Clinical Endocrinology & Metabolism, Vol. 25, No. 11, 1965, pp. 1441-1450, https://doi.org/10.1210/jcem-25-11-1441. [16] P. Pearlmutter et al., Sweat and Saliva Cortisol Response to Stress and Nutrition Factors, Scientifc Reports, 2020, pp. 1-11, https://doi.org/10.1038/s41598-020-75871-3. [17] S. Clifton et al., Salivary Testosterone Levels and Health Status in Men and Women in the British General Population: Findings from the Third National Survey of Sexual Attitudes and Lifestyles (Natsal-3), J Clin Endo Metab, Vol. 101, No. 11, pp. 3939-51, https://doi.org/10.1210/jc.2016-1669. [18] J. Y. Moon et al., Reference Ranges for Urinary Levels of Testosterone and Epitestosterone, Which may Reveal Gonadal Function, in a Korean Male Population, The Journal of Steroid Biochemistry and Molecular Biology, Vol. 140, 2014, pp. 100-105, https://doi.org/10.1016/j.jsbmb.2013.12.001.